FORMATION ENVIRONMENTAL COMPETENCE OF KAZAKHSTAN STUDENTS - Aliyeva, Aiman; Gani, Abilbekov (European Scientific Journal, ESJ, 2014)
The authors analyse the level of environmental competence of students and their role in solving ecological problems, as there is a threat of environmental hazard in many regions of Kazakhstan and worldwide. Respondents are aware of environmental problems, however, they do not have a sufficient level of environmental competence and perceive ecological issues as scientific concepts and absolutely sure that their personal opinion has no effect on the solution of environmental problems, that it’s beyond their control. As a result, we specified that the most active part of society is young people at the age of 17 - 19 years old, directed to participate in environmental activities. The total analysis of all received questionnaire data enables to ascertain various levels of environmental competence among students.